Determinants of Work-Related Risks among Veterinary Clinical Students in South West Nigeria - Oluwawemimo O. Adebowale; Monsurat O. Afolabi; Hezekiah K. Adesokan; Olubunmi G. Fasanmi; Olanike K. Adeyemo; Olajoju J. Awoyomi; Folorunso O. Fasina (Veterinary Medicine International)
Veterinary practices or activities expose professionals, including students, to hazards associated with animal contact. To describe workplace health and safety status and risk factors associated with hazards among veterinary clinical students in South West Nigeria, a cross-sectional survey was conducted using a semistructured questionnaire. Data on demographics, health and safety (HS) status, work-related hazards, healthcare facilities, and immunisation history were obtained. Of 167 students recruited, 100 (60.2%) were males, and >77.1% fell within the age group of 21–25 years. Many participants (77.0%) reported the lack of active HS committee. Exposures to various physical hazards (PHs) such as needlestick injuries (NSIs, 41.5%), animal scratches (42.0%), animal kicks (33.0%), falls/slips (25.0%), and, less frequently, animal bites (13.8%) were reported. Allergies (35.9%) and acute gastrointestinal infection (25.6%) mainly after contact with dogs presented with parvoviral enteritis were reported. For chemical hazards, 27.8% and 29.0% of participants indicated having had eye burn and choke on exposure to formalin. No adequate immunisation against either tetanus, rabies, or both was provided (<18%). An association between accommodation type and students’ level of health and safety training was observed (OR = 0.46, 95% CI: 0.241–0.897, p=0.02), and frequencies of student contact with various animal types were strongly associated with exposures to different physical and biological risks (p<0.05). This study revealed poor health and safety training, practices, and increased exposure of students to a wide range of hazards. Therefore, the development of mitigation programmes in veterinary schools becomes critical to safeguard students’ wellbeing.